Multi-proxy archaeological investigations of a Middle Palaeolithic occupation context in Eastern Transylvania, Romania. (20th August 2018) - Cosac, Marian; Murătoreanu, George; Veres, Daniel; Niţă, Loredana; Schmidt, Christoph; Hambach, Ulrich; Alexandru, Radu; Cuculici, Roxana; Buzea, Dan Lucian; Mărgărit, Monica; Dumitraşcu, Valentin; Vasile, Ştefan; et al.
Abstract: Until recently, the cave-based Middle Palaeolithic in Romania offered almost exclusively archaeological collections without chronological control, the limited number of radiocarbon samples reported usually lacking a precise archaeological context. In an effort to improve such limitations, we initiated an interdisciplinary research of the archaeological profile Abri 122 – Varghis (Vârghiş) Gorges (Romania), a site that so far produced the most important Middle Palaeolithic lithic assemblage in the Carpathian region. Initial archaeological research in the karst system of Varghis Gorges dates back to the beginning of the 20th century. For the most part, the archaeological collections recovered, although consistent, remained unpublished. The lithic analysis presented here discusses one of the richest such collections, hosted in the Székely National Museum and recovered from Abri 122 site during previous excavations, complemented by our own survey during last years. It appears that the main raw material used for tool making was quartzite, followed by lydite, opal, and volcanic rocks. Blank production seems to have favored medium to large size flakes, irrespectively of the chosen raw material. Alongside partially retouched flakes and blades, the formal tools category includes sidescrapers, endscrapers, unifacial and bifacial points. Unlike the majority of the unmodified quartzite blanks, formal tools are mainly made of lydite/opal and basalt/andesite. Albeit the archaeological material appears scattered throughout the entire vertical span, two main clusters of lithics are apparent in the newly surveyed profile. The recovered faunal remains belong to herbivores such as Bos/Bison and Capra, canids ( Canis lupus ) and cave bears ( Ursus spelaeus ). Several bone items show traces of defleshing and intentional use. Establishing a reliable chronological framing for the archaeological sequence at Abri 122 proved rather challenging. While radiocarbon dating was complicated by scarcity of collagen in bone remains and age of samples at or beyond the upper limit of the method, the upper span of the Middle Palaeolithic assemblages at Abri 122 likely reaches into Marine Isotope Stage (MIS) 3. Optically (OSL) and infrared stimulated luminescence (IRSL) dating of silt-sized grains indicate ages of >100 ka for the lowermost cluster of lithics/bones. These ages must be regarded as maximum ages for the Middle Palaeolithic assemblage at Abri 122.